The Abundance and Function of Neutrophils in the Endometriosis Systemic and Pelvic Microenvironment - Xinlei Wang; Yan Jia; Danyang Li; Xiaopin Guo; Zhengjie Zhou; Mingran Qi; Guoqiang Wang; Fang Wang (Hindawi Limited, 2023)
Endometriosis is a common inflammatory illness in which endometrial tissue grows outside the uterine cavity. Immune dysfunction is now widely acknowledged as the primary cause of endometriosis. The immune cell population represented by neutrophils is thought to play an essential role in the etiology, pathophysiology, and associated clinical outcome. There is growing evidence that neutrophils have a role in chronic and aseptic inflammatory diseases, and endometriosis patients have increased levels of neutrophils in plasma, peritoneal fluid, and ectopic endometrium. Here, we sought to review the function of neutrophils in the pathogenesis of endometriosis, with an emphasis on the role of neutrophils in regulating endometrial angiogenesis and the local inflammatory microenvironment.